2015
DOI: 10.1038/nmat4512
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of water at the SrO surface of ruthenates

Abstract: While perovskite oxides hold promise in applications ranging from solid oxide fuel cells to catalysts, their surface chemistry is poorly understood at the molecular level. Here we follow the formation of the first monolayer of water at the (001) surfaces of Srn+1RunO3n+1 (n = 1, 2) using low-temperature scanning tunneling microscopy, X-ray photoelectron spectroscopy, and density functional theory. These layered perovskites cleave between neighboring SrO planes, yielding almost ideal, rocksalt-like surfaces. An… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 51 publications
12
61
0
1
Order By: Relevance
“…The dissociation into an (OH) ads fragment, adsorbed on a cation bridge site, and into a proton, adsorbed on a neighboring surface oxygen, was recently observed on the SrO-terminated surface of Sr n+1 Ru n O 3n+1 ( n  = 1,2) 19 . There the oxygen octahedra are not tilted with respect to the [001] direction, hence the surface oxygen sublattice is square and all bridge sites are equally spaced from the O surf .…”
Section: Discussionmentioning
confidence: 83%
“…The dissociation into an (OH) ads fragment, adsorbed on a cation bridge site, and into a proton, adsorbed on a neighboring surface oxygen, was recently observed on the SrO-terminated surface of Sr n+1 Ru n O 3n+1 ( n  = 1,2) 19 . There the oxygen octahedra are not tilted with respect to the [001] direction, hence the surface oxygen sublattice is square and all bridge sites are equally spaced from the O surf .…”
Section: Discussionmentioning
confidence: 83%
“…9 A recent scanning tunneling microscopy study also underscored the important role of the RuO 6 octahedra for understanding water molecule adsorption at the ruthenate surfaces. 39 In particular, the structural flexibility or "rigidity" of the octahedra in perovskite oxides was identified as the key factor influencing molecular adsorption. The exact difference between the orthorhombic and tetragonal SRO surfaces at the molecular level is yet to be discovered, in terms of difference in bonding character and possible surface superstructures.…”
mentioning
confidence: 99%
“…Water adsorption on other materials, such as TiO 2 , SrO, Al 2 O 3 , and MgO, has been widely reported. Both experimental and theoretical approaches have revealed that there are two different modes through which the water molecule can adsorb on the solid surface: the molecular adsorption and dissociative adsorption .…”
Section: Introductionmentioning
confidence: 99%
“…There is not much information about initial water adsorption on C 2 S surfaces, which is extremely important to better understand the hydration process. 4 Water adsorption on other materials, such as TiO 2 , 10 SrO, 11 Al 2 O 3 , 12 and MgO, 13 has been widely reported. Both experimental and theoretical approaches have revealed that there are two different modes through which the water molecule can adsorb on the solid surface: the molecular adsorption and dissociative adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation